A novel anatomy and ultrasound curriculum improves physiatry resident confidence with ultrasound-guided musculoskeletal and spasticity procedures (Canadian Medical Education Journal, 2025)
Our novel anatomy and ultrasound curriculum, integrating cadaver lab sessions and ultrasound workshops, enhances resident knowledge, confidence, and competence with ultrasound-guided procedures. Physiatry educators can adopt this longitudinal approach, incorporating spaced repetition and peer learning, to improve ultrasound training. Implementing this curriculum may lead to increased proficiency in ultrasound-guided procedures among residents. For programs without access to a cadaver lab, the curriculum can be modified by using available anatomical models or online cadaveric dissection videos. The minimum resources for programs wishing to implement a similar curriculum include an ultrasound machine and a faculty member for instruction.